REFLECTION AS A COMPONENT OF PROFESSIONALIZATION PROCESS BY MEANS OF PROJECT ACTIVITY OF A STUDENT - Kazhikenova, G.M. (Publisher of Kostanay Regional University named after Akhmet Baitursynov, 2022)
Modern requirements for the educational process involve the development of a personality ready for productive interaction with the outside world, developed abilities for self-knowledge, self-development and self-improvement. Reflective skills are the basis of such important professional qualities of a person as: the ability to abstract, confidence in one's own actions, critical thinking. The project activity of a student affects the level of formation of reflection, as it has a significant impact on the further professional development and self-realization of a specialist.
Keywords: Reflective activity; professional development; project activity; self-development